KAZAKHSTAN IN THE ARAB SPRING CONTEXT - BAYDAROV, Erkin; AMIRBEKOVA, Sagynysh; ILYASSOVA, Zibagul; BATYRKHAN, Bolatbek (CENTRAL ASIA AND THE CAUCASUS, 2019)
The authors have analyzed the Arab Spring, which caused an outburst of radical Islamism and echoed in the sociopolitical and economic context of Central Asia. This subject has gained significance due to the rising extremism that threatens the national security of the Republic of Kazakhstan. The authors have aimed to delineate general provisions and specific situations related to the problem of extremism in Kazakhstan, as well as the measures needed to lower the level of radicalization among different population groups, particularly the younger generation, and prevent their involvement in terrorist activities. This is achieved through three main tasks: to explain how the Arab Spring affected Central Asia, particularly in the form of terrorist activities; to reveal the global nature of religious extremism and the measures needed to prevent its spread among the younger generation while protecting the country against terrorist ideologies; and to create and improve the legal, normative, organizational, and other mechanisms of power in Kazakhstan designed to oppose the ideology of terrorism. The analysis focuses on the driving forces and impacts of the Arab Spring, its role in the contemporary history of Kazakhstan, and the necessity of examining Kazakhstan's position in the processes pushing the world towards a new world order. The nature of radical activities in Kazakhstan and the Central Asian region has significantly changed under the influence of the Middle Eastern crisis, which has been unfolding since 2011. Today, Syria and Iraq attract mercenaries from around the world. The events in the Middle East have prompted questions about the potential for the Arab Spring to be replicated in Central Asia, whether Arab revolutions can continue in the region, and how these processes might affect it. Additionally, it raises concerns about Kazakhstan's place in the international balance of power and the implications for regional security. The impact of the Arab Spring, a multidimensional phenomenon, has spread far beyond the Middle East, affecting the interests of the United States, Russia, the European Union, Turkey, Iran, China, and other nations that share Kazakhstan’s international and geopolitical interests. Numerous authors have discussed the economic and political impacts of the Arab Spring on Central Asia as a whole and on Kazakhstan in particular. This topical subject attracts the attention of politicians and analysts from various countries. This article contributes to the collective effort by examining the lessons of the Arab Spring from a different perspective: after analyzing these lessons, it emphasizes the importance of working diligently to prevent the threats and spread of extremism and terrorism as primary challenges posed by the Arab Spring.